Dietary Taxifolin Protects Against Dextran Sulfate Sodium-Induced Colitis via NF-κB Signaling, Enhancing Intestinal Barrier and Modulating Gut Microbiota - Hou, Jinxiu; Hu, Mingyang; Zhang, Le; Gao, Ya; Ma, Libao; Xu, Qingbiao (Frontiers in Immunology, 2021)
Taxifolin is a natural antioxidant polyphenol with various bioactivities and has many beneficial effects on human gut health. However, little is known of its function on colitis. In this study, the protective effects of taxifolin on colitis symptoms, inflammation, signaling pathways, and colon microbiota were investigated using dextran sulfate sodium (DSS)-induced colitis mice. Intriguingly, pre-administration of taxifolin alleviated the colitis symptoms and histological changes of the DSS-challenged mice. Supplementation of taxifolin significantly inhibited the secretions of tumor necrosis factor-α, interleukin (IL)-1β and IL-6, and significantly increased the secretions of IL-10, secretory immunoglobulin A, superoxide dismutase, and immunoglobulins (IgA, IgG, and IgM) in DSS-induced colitis mice. In addition, the activation of nuclear factor kappa B (NF-κB; p65 and IκBα) signaling was significantly suppressed by taxifolin supplementation. The expression of tight junction proteins (claudin-1 and occludin) was significantly increased by taxifolin. Moreover, 16S rDNA sequencing revealed that the DSS-induced changes of colon microbiota composition and microbial functions (amino acid metabolism and MAPK signaling) were restored by taxifolin, including the decreases of the abundances of Bacteroides, Clostridium ramosum, Clostridium saccharogumia, Sphingobacterium multivorum, and the ratio of Bacteroidetes/Firmicutes, and the increases of the abundances of Desulfovibrio C21 c20 and Gemmiger formicilis at species level. In conclusion, these results revealed that dietary taxifolin has a great potential to prevent colitis by inhibiting the NF-κB signaling pathway, enhancing intestinal barrier, and modulating gut microbiota.